Tyler's Curriculum Rationale and the Reconceptualists. Interview with Ralph W. Tyler (1902-1994) - Graciela Cordero Arroyo; José María García Garduño (Universidad Autónoma de Baja California, 2004)
Ralph W. Tyler was considered one of the most influential of US educators during the last century. The purpose of this paper is to present an interview granted by Tyler to the first author of this paper in 1990. Tyler's interview is preceded by a brief analysis of his work, in the hope of shedding light on some misconceptions that Tyler's work has suffered since early 70s. The present interview may have been the only one given to an Ibero-American academician, and one of the very few in which Tyler spoke openly about what he thought of the fierce criticism launched by reconceptualists against his curriculum rationale.